The Role of Emotional Intelligence in Enhancing Transformational Leadership Effectiveness - Prayudi, Deri; Arraniri, Iqbal; Rois, Tatang (Jurnal Informatika Ekonomi Bisnis, 2025)
Emotional Intelligence (EI) has been increasingly recognized as a critical factor in enhancing leadership effectiveness, particularly within transformational leadership contexts. This study aims to explore the relationship between EI and transformational leadership effectiveness by examining how EI contributes to key leadership behaviors such as motivation, empathy, and conflict resolution. Using a qualitative approach, the research involved semi structured interviews and direct observation of 20 leaders from diverse sectors, including education, healthcare, technology, and manufacturing. The study identifies four primary EI dimensions self-awareness, emotional regulation, empathy, and social skills as key drivers of transformational leadership behaviors. Leaders with high EI demonstrated greater effectiveness in fostering positive organizational climates, motivating teams, and facilitating innovation. The results suggest that EI enhances transformational leadership by enabling leaders to better manage interpersonal relationships, respond to challenges, and create an environment of trust and collaboration. Additionally, the study highlights the importance of tailoring leadership development programs to emphasize EI competencies, particularly empathy and self regulation, to address the challenges of today’s dynamic business environment. The findings contribute to a deeper understanding of how EI can be integrated into leadership practices to improve employee engagement and organizational success. Future research should further explore the long term impact of EI on leadership effectiveness across various cultural and organizational contexts.